The 'Turnbull guidelines' proof and evidence under the Malaysian Evidence Act 1950 - Kamarudin, Abdul Rani (LexisNexis, 2003)
Turnbull guidelines is a requirement necessary as a matter of law where the case against the accused depended wholly or substantially on the correctness of one or more identifications of the accused, which is alleged by the defence to be mistaken identification. There is a possibility that a mistaken witness can be a convincing one and that a number of such witnesses could all be mistaken. The Court has accepted that evidence of identification is a category of evidence, which though admissible, is thought to be unreliable because of a risk of error. The circumstances in which the identification by each witness came to be made needs to be examined. Though recognition is thought to be more reliable than identification, mistakes in recognition of close relatives and friends are sometimes made. The requirement is in the form of a warning (caution), and provided that the caution is done in clear terms, the judge need not use any particular form of words. The quality of the identification evidence is what matters in the end. A failure to follow the guidelines is likely to result in conviction of the accused being quashed by a superior court, and an order for retrial of the case, as the omission would occasion a failure of justice. Obviously the words 'matters before it' in relation to the definition of proof in the Malaysia Evidence Act 1950 could not mean only 'evidence' but would include other matters the judge or the magistrate has to consider such as the need for special caution when appreciating the evidence of the case in question when it has to decide whether the accused has a case to answer at the close of the case for the prosecution or as to the guilt or innocence of the accused at the conclusion of the trial. The pertinent issue then is whether Turnbull guidelines is evidence or is it a matter other than evidence forming part of the 'matters before it' as to whether a fact is approved or disproved?